Numb-p72, but not Numb-p65, contributes to the trafficking of group I metabotropic glutamate receptors. Issue 11 (1st August 2018) - Wang, Na; Cai, Xin-Yu; Gao, Wei; Shen, Ying
Abstract : The protein Numb localizes to clathrin-coated vesicles and participates in the trafficking of transmembrane receptors. We previous reported that Numb promotes the presence of metabotropic glutamate receptor 1 (mGlu1) on neuronal membrane, and Numb deficiency impairs synaptic expression of mGlu1. However, the actions of different Numb isoforms on mGlu1 trafficking are unknown. Here, we found that Numb-p72 and Numb-p65 are distinctly expressed in HEK293T cells. Interestingly, Numb-p72, but not Numb-p65, binds to mGlu1α and promotes the membrane expression of mGlu1α by antagonizing its internalization. We hypothesize that the incomplete structure of Numb-p65 does not act in the same way as Numb-p72 on mGlu1 trafficking.